Философия науки: краткий энциклопедический словарь / В. А. Канке - Канке Виктор Андреевич (Омега-Л, 2008)
Экземпляры: СФ-16 (20110920) / Инвентарный номер: 39999z16 / Цена: 120.00 / Сис.шифр: 87 / Авт.знак: К 19 / ББК: 87.25